A influência das políticas de compras governamentais em relação aos aspectos da sustentabilidade e do bem-estar psicossocial na agricultura familiar de Cascavel-PR - Lachovicz Neto, Pedro (2022)
In the present dissertation, the proposed objective was to analyze the influence of government procurement policies in relation to aspects of sustainability and psychosocial well-being in family farming in the Cascavel (Paraná). To respond to the research problem and meet the objectives listed, the methodology was shaped in a qualitative detailed, exploratory, and descriptive way, as well as survey and documentary procedures. Literature and similar studies have shown models that make it possible to analyze aspects of sustainable development uniquely. In this way, the data collection had at its core three evaluation axes, composed of the VAPERCOM model, Psychological Well-Being Scale and Sustainability Barometer. In addition, from an economic point of view, it was intended to analyze the costs to the public sector, as a market guarantee tool for family farming, through the database of the 15th Logistics Battalion, a public agency that manages the Food Acquisition Program of the Brazilian Army in the Cascavel. The main results indicate that the sociodemographic profile of farmers and family members is aligned with regional sustainable development. Most of the participants in the Food Acquisition Program have a monthly profit range above three thousand reais, are linked to the National Program for the Strengthening of Family Farmers, and have diversified ways of marketing their products, such as the National School Feeding Program and Fairs that, added to the Food Acquisition Program, represent 80% of how the products are sold. Thus, it is inferred that there is a strong influence of government purchases on the sustainability of family farming in Cascavel, but it demands improvements in the relationship between the support groups and family agents. Regarding environmental perception, they have a great possibility of becoming ecological consumers, in addition to frequent concern with the life cycle of products and high environmental perception. Moreover, they have a high degree of psychological well-being, highlighting the dimensions of personal growth and purpose in life. The results of the Sustainability Barometer indicated that family farming respondents have sustainable potential. As a suggestion for future research, replication of the methodology is recommended for farmers who do not participate in government purchases and other social actors as a basis for elaborating public policies for social intervention